Pelanggaran Prinsip Kesantunan Komentar Penonton Youtube Najwa Shihab Dalam Wacana Kampanye Pemilihan Umum 2019 - Tsalisa Yuliyanti (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The development of hate speech on digital space, that is Youtube, as a group or individually. One of the YouTube channels is Najwa Shihab which discusses political issues in Indonesia, one of which is the 2019 presidential election campaign. The purpose of this study is to analyze the impoliteness principle of hate speech in the comments of Najwa Shihab's Youtube on the 2019 General Election Campaign Discourse. The research approach is a theoretical approach in the form of a forensic linguistic approach and pragmatics for data analysis, and a methodological approach that is descriptive qualitative. The data analyzed was in the form of audience commentary speech on Mata Najwa and Catatan Najwa. The results showed that there were six impoliteness principle of hate speech . The impoliteness type of civility that is widely used is the violation of the maxim of appreciation as much as 73.3% of the total number of 300 utterances. The principle of civility that is least violated is that the maxim withholds opinions by 0.7% of the total 300 utterances. The results of the research are expected to be useful for the community, especially as a reference material in avoiding violations of hate speech crimes.